PENGARUH POLARISASI DIVERSITY TERHADAP BITRATE PADA OPENLTE SISTEM - Nur, Levy Olivia; Karimafikri, Aisha Aulia; Sitorus, Saidhatul Munawaroh; Nurhaliza, Salwa (Telkom University, 2024)
The main challenge for mobile wireless operators is to ensure that users consistently receive smooth and reliableservices. One of the crucial components in the development of wireless technology is the antena. The aim ofthis research is to understand the impact of polarization diversity on bitrate in the OpenLTE system. MultipleInput Multiple Output (MIMO) antenna system can enhance capacity and transmission speed in communicationsystems. OpenLTE features include a simple eNodeB with integrated Evolved Packet Core, tools for scanningand recording LTE signals based on GNU Radio. In this study, an analysis is conducted on the effects of MIMOantenna polarization arrangements using Co-Polarization and Cross-Polarization configurations. The researchindicates that the antenna configuration significantly influences the amount of bitrate and Signal to Noise Ratio(SNR) produced. The Cross-Polarization configuration can achieve a relatively high bitrate of 38 Mbps duringservice activities, compared to Co-Polarization, which only yields 28 Mbps in terms of birtare.